Adaptation of the Jarawa to Andaman Islands - Kumar, Umesh (Brill | Manohar Publishers & Distributors, 2023)
Hunting and gathering constitute the oldest human mode of subsistence and the only one for which there is an uninterrupted record from the human origins to the present. Today, there are a handful of hunter-gatherers who subsist exclusively through the hunting of wild animals, fishing, and gathering of wild plants. The Jarawa of the Andaman Islands are one among them. Within the spectrum of foraging societies, the Jarawa belong to the category of 'immediate return' foragers, as they tend to consume most of the food resources immediately. The present study provides a detailed account of the foraging and adaptive strategies of the Jarawa. The interaction of the Jarawa with the outside world is one of multifaceted inequality which places them in an extremely weak position against the outsiders. The hunting-gathering societies appear extremely vulnerable in the event of a direct or indirect threat from various forces, particularly encroachment of their territories by 'others', invasion of modernization, etc., as an aftermath of contact with the outsiders. The current work discusses the impact of contact on the resource base, health, population, habits, and material culture of the Jarawa in the post-hostility phase (post-1997 period). The present work on the Jarawa will be of immense help to researchers studying human adaptation in the remote past. Furthermore, it will also help administrators and policymakers in designing meticulous policies for the protection and development of Particularly Vulnerable Tribal Groups of India.